The viability of the rhetorical tradition - Graff, Richard, 1968-; Walzer, Arthur E., 1944-; Atwill, Janet, 1955- (State University of New York Press, 2005)
"The Viability of the Rhetorical Tradition reconsiders the relationship between rhetorical theory, practice, and pedagogy. Continuing the line of questioning begun in the 1980s, contributors examine the duality of a rhetorical canon in determining if past practice can make us more (or less) able to address contemporary concerns. Also examined is the role of tradition as a limiting or inspiring force, rhetoric as a discipline, rhetoric's contribution to interest in civic education and citizenship, and the possibilities digital media offer to scholars of rhetoric."--Jacket